Fermented Foods as Functional Systems: Microbial Communities and Metabolites Influencing Gut Health and Systemic Outcomes - Inmyoung Park; Mohamed Mannaa (Foods)
Fermented foods represent an intricate ecosystem that delivers live microbes and numerous metabolites, influencing gut health. In this review, we explore how complex microbial communities and metabolites generated during food fermentation modulate the gut microbiome and affect human health. We discuss fermentation-induced biochemical transformations, including enhanced fiber fermentability; nutrient availability; and the synthesis of bioactive metabolites such as short-chain fatty acids, exopolysaccharides, bacteriocins, and modified polyphenols. We describe the dynamic microbial ecology of fermented foods, influenced by ingredient variations, highlighting its effect on health-related metabolic outcomes. Fermented products when consumed transiently introduce beneficial microbes and bioactive compounds into the gut, thereby boosting microbial diversity, resilience, and barrier function. We review clinical and preclinical studies to substantiate the roles of fermented foods in immune regulation, metabolic homeostasis, cognitive function, and inflammation mitigation. Individual variability in response to fermented foods has been emphasized, underscoring the potential for personalized nutrition strategies informed by advanced omics technologies. By integrating microbial ecology, metabolomics, and clinical evidence, this review positions fermented food intake as a strategic dietary intervention for microbiome modulation and health promotion.